KEEFEKTIFAN MODEL PEMBELAJARAN MIND MAPPING DAN PICTURE AND PICTURE BERBANTU MEDIA PUZZLE TERHADAP HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - pratami, Ainunnisa Nabila; Shodiqin, Ali; Listyarini, Ikha (JGK (Jurnal Guru Kita), 2019)
Abstract: Effectiveness of Mind Mapping and Picture and Picture Learning Models assisted by Media Puzzle on Learning Outcomes of Class V Elementary School Students. This study aims to determine the effectiveness of the Mind Mapping and Picture and Picture learning models supported by Puzzle media on the learning outcomes of fifth grade students in science subjects in Doropayung 02 Elementary School, Pati Regency. This type of research is an experimental type quantitative research with posttest only control design technique. The population of this study was fifth grade students at SD Negeri Doropayung 02 Pati Regency. Retrieving data using observation, documentation and multiple choice tests. In hypothesis 1 there are differences in student learning outcomes in Heat or Heat Transfer material. In hypothesis 2, it is found that the Mind Mapping learning model is better than the conventional learning model. In hypothesis 3 it was found that the Picture and Picture learning model was better than the conventional learning model. In hypothesis 4, it is found that the Mind Mapping learning model is better than the Picture and Picture learning model. This shows the use of the Mind Mapping model and Picture and Picture media-assisted Puzzle effective on the learning outcomes of students of science subjects. Keyword : Mind Mapping, Picture and Picture, Puzzle Media, Learning Outcomes Abstrak : Keefektifan Model Pembelajaran Mind Mapping dan Picture and Picture berbantu Media Puzzle terhadap Hasil Belajar Siswa Kelas V Sekolah Dasar. Penelitian ini bertujuan untuk mengetahui keefektifan model pembelajaran Mind Mapping dan Picture and Picture berbantu media Puzzle terhadap hasil belajar siswa kelas V pada mata pelajaran IPA di SD Negeri Doropayung 02 Kabupaten Pati. Jenis penelitian ini adalah penelitian kuantitatif tipe eksperimen dengan teknik posttest only control design. Populasi penelitian ini adalah siswa kelas V di SD Negeri Doropayung 02 Kabupaten Pati. Penggambilan data menggunakan observasi, dokumentasi dan test pilihan ganda. Pada hipotesis 1 terdapat perbedaan hasil belajar siswa pada materi Perpindahan Kalor atau Panas. Pada hipotesis 2 diperoleh bahwa model pembelajaran Mind Mapping lebih baik daripada model pembelajaran konvensional. Pada hipotesis 3 diperoleh bahwa model pembelajaran Picture and Picture lebih baik daripada model pembelajaran konvensional. Pada hipotesis 4 diperoleh bahwa model pembelajaran Mind Mapping lebih baik daripada model pembelajaran Picture and Picture. Hal ini menunjukkan penggunaan model Mind Mapping dan Picture and Picture berbantu media Puzzle efektif terhadap kemampuan hasil belajar siswa mata pelajaran IPA. Kata Kunci : Mind Mapping, Picture and Picture, Media Puzzle, Hasil Belajar